2004
DOI: 10.1037/1076-8971.10.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Guided jury discretion in capital murder cases: The role of declarative and procedural knowledge.

Abstract: This article analyzes whether state-approved jury instructions adequately guide jury discretion in the penalty phase of first-degree murder trials. It examines Eighth Amendment jurisprudence regarding guided jury discretion, emphasizing the use of “empirical factors” to examine the quality of state-approved instructions. Psychological research and testimony on the topic of the comprehensibility of jury instructions are reviewed. Data from a recently completed simulation with 80 deliberating juries showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…Instruction comprehension data support previous findings which suggest there are major problems with the comprehensibility of capital penalty instructions (e.g., Diamond & Levi, 1996; Geimer & Amsterdam, 1988; Haney, 1995; Haney & Lynch, 1994, 1997; Haney, Sontang, & Costanzo, 1994; Luginbuhl & Howe, 1995; Tiersma, 1995; Wiener et al, 1995; 2004). Specifically, it is troubling to note how often participants make pro-prosecution errors in instruction comprehension, such as the finding that almost half of our sample (44.6%) incorrectly thought that a death sentence was mandatory when the jury unanimously finds aggravating circumstances.…”
Section: Study 1: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Instruction comprehension data support previous findings which suggest there are major problems with the comprehensibility of capital penalty instructions (e.g., Diamond & Levi, 1996; Geimer & Amsterdam, 1988; Haney, 1995; Haney & Lynch, 1994, 1997; Haney, Sontang, & Costanzo, 1994; Luginbuhl & Howe, 1995; Tiersma, 1995; Wiener et al, 1995; 2004). Specifically, it is troubling to note how often participants make pro-prosecution errors in instruction comprehension, such as the finding that almost half of our sample (44.6%) incorrectly thought that a death sentence was mandatory when the jury unanimously finds aggravating circumstances.…”
Section: Study 1: Discussionsupporting
confidence: 83%
“…Speaking specifically to the issue of instruction comprehension, the current studies replicate prior research demonstrating alarmingly low levels of jury comprehension of actual capital sentencing instructions (see, e.g., Haney & Lynch, 1994; 1997; Luginbuhl, 1992, Luginbuhl & Howe, 1995, Wiener et al, 1995; 1998; 2004), and also support the promising findings suggesting that the comprehensibility of capital sentencing instructions can be improved (e.g., Diamond & Levi, 1996; Otto, Applegate, & Davis, 2007; Smith & Haney, 2011; Wiener et al, 1995; 1998; 2004). While we observed abysmally low comprehension for the pattern Virginia instructions, comprehension was markedly higher when participants received revised instructions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Specifically, it has been found that instructions often are confusing due to the inclusion of double negatives, ambiguous language, and legal terms that are unknown to the jurors (Diamond, 1993). Furthermore, Wiener et al (2004) demonstrated that mock jurors do not understand many of the central concepts in capital jury instructions and that the process of deliberation does not increase the level of comprehension among jurors. Crucial terms such as ''aggravating'' and ''mitigating'' are frequently misunderstood, as is the process of ''weighing'' the two groups of factors against each other (Costanzo, 1997;Fleury-Steiner, 2005).…”
Section: Racial Bias In the Penalty Phase Of Capital Trialsmentioning
confidence: 97%
“…Furthermore, some evidence suggests that standard pattern instructions might not only fail at explaining to jurors their duties, but actually make jurors less likely to understand these duties, compared to jurors who rely on lay interpretations of legal concepts (Wiener et al, 2004 ). For example, mock jurors presented with standard jury instructions reported lower rates of comprehension of concepts such as aggravators and mitigators, compared to mock jurors who were not given any defi nition of aggravators and mitigators (Wiener et al, 2004 ).…”
Section: The Psychological Perspectivementioning
confidence: 99%